MEDIA KOMUNIKASI SANTRI DAN ALUMNI PONDOK PESANTREN ROBITHOTUL ASHFIYA' BERBASIS WEBSITE - Assani, Saffana; Afiyat, Nur; Hermanto, Hermanto; Maulana, Dhimas Abdu; Santoso, Fandi Ahmad; Zaimuddin, Ahmad (Jurnal Difusi Ipteks Legowo, 2023)
Founded in 1990, Robithotul Ashfiya Islamic Boarding School has had students spread across the archipelago. However, the communication media between alumni and students are still limited to social media such as FB and What’sapp group. This makes information often not well-conveyed and well-documented. Since the place is located quite far from the city center, this Islamic boarding school is not well-known by the public, so it requires qualified promotional media. With the establishment of cooperation between the Islamic boarding schools and Universitas Qomaruddin, a solution is found to the existing problems, namely the realization of a boarding school website. The system development methodology used is SDLC (System Development Life Cycle). Feasibility studies and investigations are carried out directly to the site. Requirement analysis includes functional and non-functional requirements of the system. System design uses UML (Unified Modeling Language) and level diagrams. Application is in the form of system development using the CMS (Content Management System) wordpress and system implementation. Regular review and maintenance are with a direct mentoring system in the form of system management training and monitoring system use. The result of the community service is a finished product of a boarding school website and website management training for the boarding school system administrators. With the existence of the website, now the Robithotul Ashfiya Islamic boarding school can make promotions to the community more easily and provide better information to its students and alumni.